Formation pressure distribution and productivity prediction of fractured horizontal wells in stress sensitive reservoirs - Huzhen, Wang; Tiancheng, Liu; Zhuangzhuang, Sun; Chunyao, Wang; Zhenyu, Liu; Zhijun, Zhou; Changjun, Diao; Zhiming, Zhao (Frontiers in Energy Research, 2022)
Aiming at the problems of formation pressure distribution and productivity change after horizontal fracturing in stress-sensitive reservoirs, dynamic permeability and dynamic starting pressure gradients were used to deal with the stress sensitivity, an oil-water two-phase numerical calculation method based on the finite element method was established. History matching is performed on the basis of the prediction of formation pressure distribution after volume fracturing of horizontal wells, which ensures high matching accuracy. Taking the ultra-low permeability sandy conglomerate reservoir of Baikouquan Formation in M18 area of Aihu Oilfield as research object, the influence of formation pressure level and stress sensitivity on formation pressure distribution and oil well productivity was studied. Calculations proves that：the effect of formation pressure level on well productivity is mainly in the first year of production, and the effect of energy increasing by volume fracturing is clarified. Stress sensitivity mainly affects the middle and later stage of production. With the increase of sensitivity, the permeability loss of the formation tends to be concentrated in the low-pressure area near the artificial fracture, forming an isolation zone with high flow resistance, which make the exploitation effect of far well zone worse.